Effects of Processing Parameters on Flow-Induced Crystallization of iPP in Microinjection Molding - Zhang, Jie; Guo, Chao; Wu, Xian; Liu, Fanghui; Qian, Xinyuan (Journal of macromolecular science. Physics, 2011)
Flow-induced crystallization has long been an important subject in polymer processing. Varying processing conditions can produce different morphologies, which lead to different properties. Recent studies have indicated that the final morphology is, in fact, dictated by the formation of crystallization structures under flow. This study deals with the influence of processing parameters on the polymorphism and crystallization orientation of isotactic polypropylene (iPP) in microinjection molding. Crystallinity and polymorphism were investigated by means of differential scanning calorimeter (DSC) and one-dimensional wide-angle X-ray diffraction (1D-WAXD). Crystalline orientation was characterized by two-dimensional wide-angle X-ray diffraction (2D-WAXD). Herman's orientation functions determined from the flat-plate wide-angle X-ray diffraction patterns were used to evaluate the orientation level of microparts. It was found that the effect of processing parameters on the crystallinity was not obvious, but these processing parameters had a great influence on the β-modification content of microparts. When the mold temperature was 150°C, β-modification still formed in microparts because the thermal stability of the β-modification was enhanced with increasing the mold temperature; The β-modification content of microparts decreased obviously when the injection time was 1 s compared to the longer injection time. However, the β-modification content of microparts increased with increasing the injection pressure. In addition, the γ-modification existed in the microparts at the mold temperatures of 150 and 160°C. From Herman's orientation functions, we know that the influence of processing parameters on α-crystalline orientation in microparts was small. But the processing parameters can affect the degree of the β-modification orientation. A shish-kebab structure was observed in some regions throughout the longitudinal sections of all the microparts by the SEM analysis.